Simvastatin interferes with cancer 'stem-cell' plasticity reducing metastasis in ovarian cancer. Issue 10 (October 2018) - Kato, S; Liberona, M F; Cerda-Infante, J; Sánchez, M; Henríquez, J; Bizama, C; Bravo, M L; Gonzalez, P; Gejman, R; Brañes, J; García, K; Ibañez, C; et al.
Abstract : Cell plasticity of 'stem-like' cancer-initiating cells (CICs) is a hallmark of cancer, allowing metastasis and cancer progression. Here, we studied whether simvastatin, a lipophilic statin, could impair the metastatic potential of CICs in high-grade serous ovarian cancer (HGS-ovC), the most lethal among the gynecologic malignancies. qPCR, immunoblotting and immunohistochemistry were used to assess simvastatin effects on proteins involved in stemness and epithelial-mesenchymal cell plasticity (EMT). Its effects on tumor growth and metastasis were evaluated using different models (e.g., spheroid formation and migration assays, matrigel invasion assays, 3D-mesomimetic models and cancer xenografts). We explored also the clinical benefit of statins by comparing survival outcomes among statin users vs non-users. Herein, we demonstrated that simvastatin modifies the stemness and EMT marker expression patterns (both in mRNA and protein levels) and severely impairs the spheroid assembly of CICs. Consequently, CICs become less metastatic in 3D-mesomimetic models and show fewer ascites/tumor burden in HGS-ovC xenografts. The principal mechanism behind statin-mediated effects involves the inactivation of the Hippo/YAP/RhoA pathway in a mevalonate synthesis-dependent manner. From a clinical perspective, statin users seem to experience better survival and quality of life when compared with non-users. Considering the high cost and the low response rates obtained with many of the current therapies, the use of orally or intraperitoneally administered simvastatin offers a cost/effective and safe alternative to treat and potentially prevent recurrent HGS-ovCs.